2013
DOI: 10.1177/0954008312469235
|View full text |Cite
|
Sign up to set email alerts
|

Study on constructional design and structural analysis of poly(amide-imide)/ZnO nanocomposites containing pyromellitoyl-bis-l-isoleucine moieties

Abstract: Hybrid nanocomposites (NCs) produced by the dispersion of zinc oxide (ZnO) nanoparticles (NPs) in thermoplastic poly(amide-imide)s (PAIs) are designed and synthesized using ultrasonic-assisted technology. ZnO NPs were functionalized with 3-aminopropyltriethoxysilane (KH550) coupling agent to increase the hydrophobic nature of NPs. Reaction of diamine containing N-(4-hydroxyphenyl) benzamide and a diacid chloride comprising pyromellitoyl-bis-L-isoleucine segments at low temperature provided the polymeric matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The most common technique for surface treatment of NPs is the application of commercial silane coupling agents or other organic molecules composed of alkoxysilane linkages using ultrasonic method in altered media . In the first step, CeO 2 NPs were modified with HDTMS using ultrasonic assisted process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common technique for surface treatment of NPs is the application of commercial silane coupling agents or other organic molecules composed of alkoxysilane linkages using ultrasonic method in altered media . In the first step, CeO 2 NPs were modified with HDTMS using ultrasonic assisted process.…”
Section: Methodsmentioning
confidence: 99%
“…In the first step, CeO 2 NPs were modified with HDTMS using ultrasonic assisted process. CeO 2 NPs were dried out at 120°C in an oven for 48 h. Then the 0.20 g dried nano CeO 2 was sonicated for 15 min in absolute ethanol, then 0.03 g HDTMS was added to the mixture and sonicated for 20 min . The product was separated and dried at 60°C for 24 h. The PAA was sonicated in ethanol for 20 min and then obtained colloidal solution was mixed with the appropriate amount of treated CeO 2 NPs to make 4, 8, and 12 wt% based on the PAA content.…”
Section: Methodsmentioning
confidence: 99%
“…Poly(amide-imide)s (PAIs) are known for their excellent mechanical strength, high temperature stability, and good chemical resistance, which qualify them as highperformance polymeric materials for preparation of nanocomposites as showed in our previous studies. [1][2][3][4][5][6][7][8] Since the introduction of first polymer nanocomposites using carbon nanotubes (CNTs) as filler by Ajayan et al in 1994, many investigations have been directed at developing CNT nanocomposites to achieve superior properties compared to the base polymer. [9][10] The growing interest in the use of CNTs is linked with a unique structure and chemical properties of CNTs such as low density, excellent mechanical, electrical, thermal properties, and a high surface area to volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the NPs were dispersed homogeneously in the PAI matrix, thereby improving thermal properties of the obtained NCs. 25,26 In this study, we attempted to report the synthesis and characterization of novel optically active PAI/Al 2 O 3 NCs through the ultrasonic method under green conditions. New PAI was fabricated using direct polycondensation of N-trimellitylimido-L-phenylalanine (DAF) with 1,5naphthalene diamine (NDA) under conventional heating in the presence of tetrabutylammonium bromide (TBAB) and TPP as the activators.…”
Section: Introductionmentioning
confidence: 99%